RAMBU PEMBELAJARAN DANPENILAIAN SASTRA ANAK - Burhan Nurgiyantoro (Jurnal Cakrawala Pendidikan, 2007)
Efforts to develop children's personality to the optimum should be made viavarious aspectsmlife, one of which is children's literature. Such literature is atpresent believed to be able to significantly.contribute to the shaping of children'spersonality. Therefore,it needs to be given its proper place in the learning andlearning achievement evaluation activities at school, which is in line with what isstated in the curriculum now in use, i.e., KTSP (short for Kurikulum Tingkat SatuanPerfdidikan, which means the Curriculum at the Level of Educational Unit), forelementary school in referring tothe school subject Pendidikan Bahasa Indonesia(which means Education in the Indonesian Language).In running classes of children's literature for children of pre"school age throughto early adolescence in elementary school and early junior high school classes, oneshould pay attention to a number of significant related matters. They are, amongothers, the learning objective, type of children's literature, selection of learningstrategy, utilizationof media, development of teacher creativity, and showing ofteacher attitude expressing empathy. Evaluationis also related here becauseleartlingalways goes together with its evaluation. The techniques ofevaluation thatcOnldbe made use of are, among others, those employing quizzes, assignments,Observations, interviews,and portfolios. The learning and evaluation activities arenot -to be limited to the classroom. Most are to be done ontside the classroom bycondncting collaborations with parents